KEMAMPUAN MEMBACA AL-QUR'AN SISWA SMP NEGERIDI KABUPATEN LUWU - br Sofyan (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Luwu. Especially at SMPN 1 Belopa,SMPN 2 Suli, and SMPN 3 Belopa. The aim of this research is to describethe student ability on reading Al-Qur'an. This research usedquantitative method, where data was collected by questioner. Than,data was analyzed by statistical analysis.This research shows that indicates that ability degree on readingAl-Qur'an of those students of the three schools is commonlygood enough. Their mean score are 88.7 to 95.2. SMPN1 Belopa get the highest score (95.5), SMPN 2 Suli get middlescore (87.7), and SMPN 3 Belopa get the lowest score (78.6).This good ability was influenced by some factors, are methodin reading Al-Qur'an and the motivation of students